The relationship between education on economic growth: case in Sweden/ Noramira Halil - Halil, Noramira (2018)
As we know that each country around the world are very concern about their economic growth. Usually we know that macroeconomic variable are the component that contribute to economic growth but now it realized that human capital can be a component to economic growth especially in term of education. By having a wide knowledge, good education and training system, creative industries will lead the country to the sustainable economic development. Many researcher already highlighted that education become a significance components to pattern the gross domestic product growth. By using a multiple regression model, this study tried to reveal the role of education as a factor of growth in Sweden. This research based on the time series data that take from World Bank which are; GDP per capita, enrolment in primary, secondary and tertiary education over the period 1971-2015. All the dataset lead to similar conclusion where education related to the economic growth. At the same time the data will analyzed and determine which level of education will effects economic growth in Sweden. From the result, it suggested that improving in education system is needed to achieve higher economic growth.